Papers - Equipment for Routine Creep Tests on Zinc aid Zinc-base Alloys. and an Example of Its Application (With Discussion) - J. Ruzicka (The American Institute of Mining, Metallurgical, and Petroleum Engineers, 1937)
In creep testing, material is subjected to a constant load, preferably at a constant temperature, and its rate of deformation is measured. The method of loading can be of various types but in this paper only creep testing under tensile load will be considered. The ordinary tensile test is essentially a comparison test in conditions that frequently hear little or no relation to those under which the test material is to be used in service. The purpose of creep tests is to measure the strength of the test material at slow rates of deformation that more nearly approach the rates realized in service. One purpose of this paper is to illustrate that the creep test, in addition to its value as a service test, is superior to the ordinary tensile test as a sensitive tool for the comparison of certain metals in investigative testing. The other purpose is to describe equipment having distinctive features of design that make it especially suitable for such tests. Representative data obtained with this equipment on a group of rolled zinc-base materials are given. These data are compared with those from practical comparison tests of the creep type on weatherstrip fabricated from the same group of materials. The comparison illustrates the value of the fast creep test and of the equipment. The Equipment The creep equipment consists essentially of a tank containing a constant-temperature oil bath in which the creep of 14 specimens, loaded by means of levers, is measured by means of one movable extensometer. Figs. 1, 2 and 3 illustrate its general construction and appearance. Constant-temperalure Oil Balh.—A common constant-temperature bath requiring only one temperature-controlling equipment for a number of specimens was chosen as the best means of fulfilling the requirements of low cost and compactness. In addition, this allows the testing of a group of specimens under identical temperature conditions.